Transformative Leadership for Integrating Islamic Values and 21st Century Skills: A Conceptual Framework for Contemporary Islamic Education - Firda Prasetyowati; Ulfi Maula Saniya; Syifa Fauzia; Susilawati, Samsul (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2025)
Purpose – This study aims to propose a conceptual framework of transformative leadership that integrates Islamic values with 21st-century skills to enhance the relevance, ethical grounding, and innovation capacity of Islamic educational institutions in the digital and global era. Design/methods – The research employed a qualitative library research approach by systematically reviewing scholarly articles, books, and institutional policy documents. The method involved inductive thematic analysis to extract leadership constructs aligned with Islamic ethical paradigms and 21st-century educational competencies. Findings – The study identifies that effective transformative leadership in Islamic education must synthesize spiritual integrity, ethical governance, and future-oriented competencies. Core elements include participatory decision-making, value-based curriculum design, digital integration, and teacher empowerment grounded in Islamic pedagogical values. These strategies facilitate character formation alongside the acquisition of critical thinking, creativity, collaboration, and communication (4Cs). Research implications/limitations – This conceptual study is limited by the absence of empirical field validation. Future research should explore how the proposed model functions across diverse institutional contexts using mixed-method or case study designs to test applicability, impact, and scalability. Practical implications – The framework offers guidance for policy-makers, school leaders, and teacher educators to align leadership development, curriculum reform, and institutional transformation with both Islamic values and global skill demands. It supports strategic planning and institutional capacity-building for faith-based schools. Originality/value – This paper contributes original insight by bridging Islamic epistemology with global transformative leadership theory. It challenges the binary between religious tradition and modern innovation, presenting Islamic education as a moral-intellectual paradigm suited to contemporary educational challenges.